2021
DOI: 10.1038/s41598-021-95685-1
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic inhibition in the human visual cortex relates to eye dominance

Abstract: Binocular vision is created by fusing the separate inputs arriving from the left and right eyes. ‘Eye dominance’ provides a measure of the perceptual dominance of one eye over the other. Theoretical models suggest that eye dominance is related to reciprocal inhibition between monocular units in the primary visual cortex, the first location where the binocular input is combined. As the specific inhibitory interactions in the binocular visual system critically depend on the presence of visual input, we sought to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…Second, pharmacological inhibition of GABA synthesis or its receptors can reactivate neuroplasticity in the visual cortex of adult rats (Sale et al, 2010). Beyond its effect on plasticity, GABA has been implied directly in the intracortical (Liu et al, 2004;Ip et al, 2021) and interhemispheric (Palmer et al, 2012;Restani and Caleo, 2016;Bocci et al, 2018) suppression exerted by the dominant eye over the amblyopic. As the potential for increased plasticity in the human visual system is preserved in adult life (Lunghi et al, 2011;Lo Verde et al, 2017), the decrease in GABA levels by tDCS in the visual cortex where anodal stimulation was performed could be impacting two different aspects: increasing plasticity and preventing or alleviating the suppression exerted by the areas under the control of the dominant eye over the areas or circuits destined to be controlled by the amblyopic eye.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, pharmacological inhibition of GABA synthesis or its receptors can reactivate neuroplasticity in the visual cortex of adult rats (Sale et al, 2010). Beyond its effect on plasticity, GABA has been implied directly in the intracortical (Liu et al, 2004;Ip et al, 2021) and interhemispheric (Palmer et al, 2012;Restani and Caleo, 2016;Bocci et al, 2018) suppression exerted by the dominant eye over the amblyopic. As the potential for increased plasticity in the human visual system is preserved in adult life (Lunghi et al, 2011;Lo Verde et al, 2017), the decrease in GABA levels by tDCS in the visual cortex where anodal stimulation was performed could be impacting two different aspects: increasing plasticity and preventing or alleviating the suppression exerted by the areas under the control of the dominant eye over the areas or circuits destined to be controlled by the amblyopic eye.…”
Section: Discussionmentioning
confidence: 99%
“…Comparably, fMRI studies show that humans with amblyopia have a clear dominance of the fellow over the amblyopic eye in V1 (Hubel and Wiesel, 1970;Liu et al, 2002Liu et al, , 2004. In turn, the levels of eye dominance are correlated to the difference in GABAergic inhibition between the eyes during visual processing (Ip et al, 2021), this is, the greater the dominance of one eye over the other, the higher levels of GABA are detected during monocular stimulation of the dominant eye compared to monocular stimulation of the non-dominant eye (41). While anodal tDCS reduces GABA levels and is therapeutic when applied to both visual cortices (anode located at the occipital midline), cathodal tDCS seems to be effective only when delivered to a single cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, general data analysis for advanced MRS methods such as HERMES continue to evolve, including modeling the baseline and data fitting. The tissue correction methods carried out in this study include an α-correction to account for higher GABA in GM than WM as this method is widely used in studies examining GABA+ in the literature ( Ip et al, 2021 , Bernardino et al, 2022 , Heise et al, 2022 , Stoby et al, 2022 , Trujillo et al, 2022 ). Relative GM vs WM levels of other metabolites, such as GSH and Glu are not defined ( Srinivasan et al, 2010 , An et al, 2015 , Chan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that visual input may have an effect on ocular dominance plasticity. Recently, Ip et al [ 7 ] reported the GABA inhibition in the human visual cortex relates to eye dominance. Considering that the apoptosis of retinal ganglion cell in glaucoma results from the retrograde degeneration of retinal ganglion cell, there is possibility that retrograde suppression may occur originating from ocular dominance column corresponding to nondominant eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, macula area processed in the contralateral hemisphere was thicker in dominant eyes compared with nondominant eyes [ 2 ]. The underlying mechanism in ocular dominance involves the imbalances in gamma-aminobutyric acid (GABA) levels in the human visual cortex [ 7 ]. These evidences suggest a possibility of reciprocal feedback mechanism related to ocular dominance in the visual cortex and retina.…”
mentioning
confidence: 99%